(untitled) (Patan Pragya, 2023)
This article provides a comprehensive analysis of labor migration trends in Nepal, focusing on the significant increase in the number of laborers migrating and the government’s role in facilitating migration to new destinations. It also explores the long-term consequences of labor migration, particularly the brain drain resulting from the outflow of skilled and educated workers, and its negative impact on Nepal’s holistic development, innovation, productivity, and economic growth. This study is based on existing secondary data and used published research articles, books, and report. The article emphasizes the urgent need for comprehensive actions to safeguard the rights of migrant workers, mitigate the negative effects of labor migration, and harness its potential for sustainable development. It is found that labor migration from Nepal is a complex issue with far-reaching impacts, and it is crucial for the government, civil society, and the international community to address the challenges and risks faced by Nepali migrant workers and ensure their rights and well-being.